Best Answer

your equation is this...

2x3 + 11x = 6x

2x3 + 5x = 0

x(2x2 + 5) = 0

x = 0 and (5/2)i and -(5/2)i

Q: What is 2x3 plus 11x equals 6x?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7

2x^3-3x^2-11x+7x+32x^2-9x+16 R -41x+3 l 2x^3-3x^2-11x+7-(2x^3+6x^2)-9x^2-11x+7-(-9x^2-27x)16x+7-(16x+48)-412x^2-9x+16-[41/(x+3)]

4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9

3x - 8 = 7 so x = 5

5x + 3 = 6x + 1 Subtract 5x from both sides: 3 = x + 1 Subtract 1 from both sides: 2 = x

Related questions

If 6x + 10 = 11x , then x=2.

x=7

(4, 8)

5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7

6x + 5x = 11x

-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11

you say: 5x+7=84-6x 5x+6x+7=84-6x+6x 11x+7=84 11x+7-7=84-7 11x=77 x=77/11 x=7

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11

What are the factors? 2x3 - 8x2 + 6x = 2x(x - 1)(x - 3).

11x + 2y

11x-7

11x + 2